Common Fixed Point for Weakly Compatible Mappings on Dislocated Metric Spaces. - Hoxha, Elida (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper we prove a common fixed point theorem for multi-valued and single-valued mappings in a dislocated metric space. The set of generalized y-j weak contractive mappings considered in this paper contains the family of generalized j-weak contractive mappings as a proper subset. The theorem use weakly compatibility and psy-phy-weak contractivity condition.Itextends the work of several authors.